GAMBARAN SANITASI LINGKUNGAN DAERAH RAWAN DIARE DI WILAYAH KERJA PUSKESMAS KALUMATA TERNATE: GAMBARAN SANITASI LINGKUNGAN DAERAH RAWAN DIARE DI WILAYAH KERJA PUSKESMAS KALUMATA TERNATE - Sahnawi Marsaoly; Nur Eda Mansur (Jurnal Kesehatan, 2014)
Abstract: Diarrhea remains a global health problem, especially in developing countries. The magnitude of the problem is evident from the high morbidity and mortality due to diarrhea. The incidence of diarrhea can be caused by several factors including behavioral, environmental, and health services. WHO estimates that 4 billion cases occurring in the world and 2.2 million of them died, mostly children under the age of 5 years. Sanitation is one of the most important challenges for developing countries because according to the World Health Organisation (WHO), diarrhea diseases kill a child in this world every 15 seconds, because access to sanitation is still too low. This poses a major environmental health problem, as well as detrimental to economic growth and human resource potential on a national scale. (Anwar,2009)